The Secret History of Wonder Woman - Lepore, Jill, 1966- (Alfred A. Knopf, 2014)
A cultural history of Wonder Woman traces the character's creation and enduring popularity, drawing on interviews and archival research to reveal the pivotal role of feminism in shaping her seven-decade story.